Simulation of charge packet formation in layered polymer film. Issue 4 (1st July 2014) - H. Lean, Meng; L. Chu, Wei-Ping
Abstract : Purpose: – The purpose of this paper is to describe a rapid and robust axisymmetric hybrid algorithm to create dynamic temporal and spatial charge distributions, or charge map, in the simulation of bipolar charge injection using Schottky emission and Fowler-Nordheim tunneling, field-dependent transport, recombination, and bulk and interfacial trapping/de-trapping for layered polymer films spanning the range from initial injection to near breakdown. Design/methodology/approach: – This hybrid algorithm uses a source distribution technique based on an axisymmetric boundary integral equation method (BIEM) to solve the Poisson equation and a fourth-order Runge-Kutta (RK4) method with an upwind scheme for time integration. Iterative stability is assured by satisfying the Courant-Friedrichs-Levy (CFL) stability criterion. Dynamic charge mapping is achieved by allowing conducting and insulating boundaries and material interfaces to be intuitively represented by equivalent free and bound charge distributions that collectively satisfy all local and far-field conditions. Findings: – Charge packets cause substantial increase of electric stress and could accelerate the breakdown of polymeric capacitors. Conditions for the creation of charge packets are identified and numerically demonstrated for a combination of impulsive step excitation, high charge injection, and discontinuous interface. Originality/value: – Metallized bi-axially oriented polypropylene (BOPP) dielectric thin film capacitor with self-clearing and enhanced current carrying capability offer an inexpensive and lightweight alternative for efficient power conditioning, energy storage, energy conversion, and pulsed power. The originality is the comprehensive physics and multi-dimensional modeling which span the dynamic range from initial injection to near breakdown. This model has been validated against some empirical data and may be used to identify failure mechanisms such as charge packets, gaseous voids, and electroluminescence. The value lies in the use of this model to develop mitigation strategies, including re-designs and materials matching, to avoid these failure mechanisms.